Violencia extrema y delito en el marco de la campaña de represión clandestina en Argentina (1976–1983) - Mario Ranalletti (Amnis)
This work deals with some aspects of the trigger and the internal organization of the so called Argentinian « task groups », special units who carried out a campaign of clandestine repression against a part of the argentine people and against the guerrillas. It tries to show the link between the use of extreme violence, the commission of some crimes (theft, economic fraud, extortion) and the indoctrination received previously by special unit members. The study of these issues is done from an interdisciplinary approach (history, anthropology, psychology). The hypothesis is that this link was one of the elements which crystallized to a prolonged and intense process of indoctrination of « task groups » members; this indoctrination enabled the use of extreme violence and trivializing crimes, by the construction of a negative Otherness whose destruction would bring peace to the country. The methodology used is qualitative and comparative. The empirical basis of this work is constituted by testimonies of victims and members of the « task groups ». The theoretical framework is built from Jacques Sémelin, and Albert Bandura research’s on mass crimes and extreme violence by military and police forces. This work is one of the results of the research project « Thinking about the clandestine repression in Argentina (1955–1983) », financed by the Argentinian Universidad Nacional de Tres de Febrero, directed by the author.